Djibouti : First Review Under the Three; Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Statement by the IMF Staff Representative; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Djibouti. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The overall fiscal position improved and the reduction in domestic arrears was triple the program target. The direct impact of the global financial crisis on Djibouti has been limited. The financial system has not been affected by the global crisis, and capital adequacy has improved slightly despite increased competition. GDP growth remained strong in 2008, and inflation decelerated during the fourth quarter. The risk of external debt distress remains high. Banks remain profitable and have not been affected by the global financial crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet